Ets-2 and p53 mediate cAMP-induced MMP-2 expression, activity and trophoblast invasion - Goldman Shlomit; Staun-Ram Elsebeth; Shalev Eliezer (BMC, 2009)
Abstract Background We have previously shown that Matrix metalloproteinase (MMP) -2 is a key-enzyme in early trophoblast invasion and that Protein Kinase A (PKA) increases MMP-2 expression and trophoblast invasion. The aim of this study was to examine MMP -2 regulation by PKA in invasive trophoblasts: JAR choriocarcinoma cell-line and 6-8 w first trimester trophoblasts. Methods The effect of Forskolin (PKA) on MMP-2 expression was assessed by Northern Blot and RT-PCR. Possible transcription factors binding to consensus MMP-2 promoter sequences in response to Forskolin, were detected by EMSA binding assay and their expression assessed by western blot analysis. Antisense transfection of relevant transcription factors was performed and the inhibitory effect assessed on MMP-2 expression (RT-PCR), secretion (zymography) and trophoblast invasiveness (transwell migration assay). Results We found that Forskolin increased MMP-2 mRNA in JAR cells within 24 hours, and induced binding to p53, Ets, C/EBP and AP-2. Transcription factors Ets-2, phospho- p53, C/EBP epsilon, C/EBP lambda and AP-2 alpha bound to their respective binding sequences in response to Forskolin and the expressions of these transcription factors were all elevated in Forskolin- treated cells. Inhibition of Ets-2 and p53 reduced MMP-2 expression, secretion and invasiveness of Forskolin treated cells. Conclusion MMP-2 is regulated by PKA through several binding sites and transcription factors including Ets-2, p53, C/EBP, C/EBP lambda and AP-2 alpha. Ets-2 and p53 mediate cAMP- induced trophoblast invasiveness, through regulation of MMP-2.